'Good residents' for themselves: psychological screening and cultural imagination of future citizenship in contemporary Israel. Issue 1 (2nd January 2020) - Plotkin Amrami, Galia; Kiper, Gita
ABSTRACT: This article explores the role of mental health knowledge in selecting candidates for a high school program for potential immigrant teenagers in contemporary Israel. Analyzing how professional knowledge is applied in the selection procedures subordinated to the national Law of Return, we examine the intrinsic links between the psychological profiling and the cultural imagination of the future citizen. The article demonstrates how experts categorize students' mental conditions to predict psychological adjustment to the program and draw the boundaries of their potential citizenship, based on the cultural-political criteria of belonging. The selection procedures incorporate two forms of therapeutic governance, functioning simultaneously as a technology of risk management and of subject formation. They promote a unique kind of communal belonging – 'therapeutic citizenship', which reflects cultural tendencies in contemporary Israel, and the affective turn in the concept of citizenship. Therapeutic citizenship is based on personal wellbeing and holds value for communal interests.